Unveiling the Drivers of Audit Quality in Inspectorates: An Attribution Theory Approach on APIP Competence, Work Experience, and Independence - Prita Masyithah Khairunnisa; Fajar Gustiawaty Dewi; Pigo Nauli (PT. Altaf Publishing Corp, 2026)
This study examines internal factors influencing audit quality in Indonesian Inspectorates through the lens of Attribution Theory. Although most Inspectorates have formally achieved an advanced level of institutional capability, recurring major audit findings by the Supreme Audit Agency indicate that internal audits often fail to detect early signs of financial irregularities. Based on a review of empirical studies published between 2021 and 2024, the findings show that auditor competence and work experience consistently enhance audit quality, while auditor independence demonstrates inconsistent effects due to political and structural pressures. These results suggest that audit effectiveness depends not merely on organizational capability, but on the interaction between individual auditor attributes and the surrounding institutional environment. Scientifically, this study contributes by offering an integrative Attribution Theory–based synthesis that explains why similar internal audit capability levels produce divergent audit quality outcomes in the public sector.